2018
DOI: 10.1590/1806-9061-2017-0571
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Quality and Shelf Life of Sous Vide Cooked Turkey Cutlet Stored at 4 and 12ºC

Abstract: The aim of this study was to determine the quality and shelf life of sous vide turkey cutlet stored at 4 and 12ºC. Samples were packaged under vacuum into polyamide-polypropylene pouches, cooked using sous vide technology (65ºC/40 min), chilled at 3ºC and stored at 4 and 12ºC for 5 weeks. Microbial (TMAB, lactic acid bacteria, Enterobacteriaceae, moulds and yeasts, Salmonella spp., L. monocytogenes, Cl. perfringens), physical-chemical (pH, water activity, TBARS, L*a*b* colour, texture profile analysis and shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 23 publications
2
22
2
Order By: Relevance
“…Chicken breast fillets cooked at 60 • C at every time point showed TBARS values below one. Akoglu et al [27] reported that oxidative rancidity cannot be detected by a sensory panel under a threshold level of one (mg/kg). TBARS value was increased by increasing temperature up to 80 • C (p < 0.05).…”
Section: Lipid Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chicken breast fillets cooked at 60 • C at every time point showed TBARS values below one. Akoglu et al [27] reported that oxidative rancidity cannot be detected by a sensory panel under a threshold level of one (mg/kg). TBARS value was increased by increasing temperature up to 80 • C (p < 0.05).…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…Selecting the right temperature and time combinations plays an important role in sous vide cooking to reduce the risk of overcooking, loss of volatile compounds, and heat-sensitive nutrients [8]. In this context, the effect of cooking temperature and time in sous vide has been reported on the physicochemical properties and eating quality of pork [20][21][22][23], lamb [7], beef [24,25], turkey [26,27], and chicken [28][29][30]. Sánchez del Pulgar et al [23] found that sous vide pork cheeks cooked at 60 • C had lower water losses, more moisture content, more lightness (L*), and redness (a*) compared to those cooked at 80 • C. Roldán et al [7] reported that sous vide lamb loins cooked at 60 • C had the highest lightness and redness compared to those cooked at 70 and 80 • C. Besides, increasing cooking temperature caused an increase in cooking loss and a decrease in moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…The mean counts ranged from 1.72 to 1.88, 1.13 to 1.22 and 1.03 to 1.14 Log CFU/g, respectively. According to these results, aerobic mesophilic bacteria count in turkey cutlet of 2.05 Log CFU/g was found after cooking at 65℃ for 40 min using sous-vide machine (Akoglu et al, 2018). For study of the microbiological quality of beef steaks sous-vided at a core temperature of 70℃ for 2 min, total plate counts of 2.48 Log CFU/g were found after cooking (Bolton et al, 2000).…”
Section: Determination Of Microbial Counts Meat Quality and Sensory Attributes Of Non-inoculated Restructured Goat Steak By Sous-vide Coomentioning
confidence: 86%
“…One of the main purposes of modern packaging is to preserve the desired colour for possibly the longest period(Gazalli et al, 2013). However,Akoglu et al, (2018) reported increasing L* with increasing time in a study on Sous vide cooked Turkey cutlet stored at 4 °C and 12 ° C. The average a* level for PPT1, PPT2, HST1 and HST2 were 3.55 ± 0.75, 3.98 ± 0.52, 3.70 ± 0.96 and 3.68 ± 0.62, respectively. The average b* level for PPT1, PPT2,…”
mentioning
confidence: 90%